2020
DOI: 10.1111/jvim.15866
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical and magnetic resonance imaging follow‐up of dogs with osseous‐associated cervical spondylomyelopathy

Abstract: Background: Osseous-associated cervical spondylomyelopathy (OA-CSM) is a complex disorder with limited long-term survival. The longitudinal progression is currently unknown. Objective: To describe changes on magnetic resonance imaging (MRI) over a 2-year minimum period. We hypothesized that spinal lesions would progress in the majority of dogs. Animals: Eleven dogs previously diagnosed with OA-CSM were prospectively studied. Nine dogs were treated medically, whereas 2 were treated surgically. Methods: Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…However, a long-term MRI study of dogs with OA-CSM did not observe intervertebral disc protrusions in dogs with intervertebral disc degeneration and articular process degenerative changes after a median period of 30 months. 22 The percentage of dogs with extradural intraspinal cysts (25%) was similar to previous reports in OA-CSM. 1,4 In the present study, most of these dogs had cysts that were partially responsible for spinal cord and/or nerve root compression, although their long-term relevance is unknown.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, a long-term MRI study of dogs with OA-CSM did not observe intervertebral disc protrusions in dogs with intervertebral disc degeneration and articular process degenerative changes after a median period of 30 months. 22 The percentage of dogs with extradural intraspinal cysts (25%) was similar to previous reports in OA-CSM. 1,4 In the present study, most of these dogs had cysts that were partially responsible for spinal cord and/or nerve root compression, although their long-term relevance is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, two longterm follow-up studies of OA-CSM dogs using CT (median follow-up time 28 months) or MRI (median follow-up time 30 months) found that while imaging changes and clinical signs were likely to continue progressing slowly after diagnosis, a worsening of morphologic changes did not necessarily equate to a worsening of neurologic grade. 21,22 It is possible that OA-CSM is a genetically complex disease and that these younger dogs with more severe changes are a reflection of more severe, yet undetermined genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that although surgical management frequently resulted in neurologic improvement and offered a better long‐term prognosis, some medically managed dogs still had a good quality of life for several years 3 . Similarly, recent studies have demonstrated slow or no notable progression of clinical signs and imaging findings in dogs with OA‐CSM that were available for a follow‐up period of at least 18 months 11,12 …”
Section: Figurementioning
confidence: 99%